A Miniature RFID Antenna at UHF Band using Meander-Line Technique - Y. Gmih; Y. El Hachimi; M. Makroum; A. Fachi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper displays a new design of a small antenna proposed for radio-frequency identification (RFID) applications in the UHF band (ultra-high frequency). Our antenna is constituted of two rectangular patches linked together with a meander line. Using this technique reduction in antenna size of equal to 62% with respect to the conventional antenna was achieved. The antenna has a simple structure and small antenna size of 60 x 74mm2 or 0.184 λ0 x 0.226 λ0. It has been fabricated on a low-cost FR4 substrate and measured to validate the simulation performances.The measured bandwidth is around 54.4 MHz (889.3 - 943.7 MHz) with reflection coefficient less than 10 dB, which covers all of the American RFID band (902 - 928 MHz), Chinese RFID band (920.5 - 924.5 MHz), Korea Republic and Japan RFID band ( 917 - 923.5 MHz).The design and simulations have been effected by electromagnetic simulators HFSS and CST microwave studio. A good accord is getting between the simulated and measured results. This antenna is intended for the reader of RFID applications.